A study on PVDF-PEO-Li7La2.5Ce0.5Zr1.625Bi0.3O12 solid electrolyte with high ionic conductivity and its application in solid-state batteries - Jing Wang; Xin Li; Xinlu Wang; Yang Su; Guixia Liu; Wensheng Yu; Xiangting Dong; Jinxian Wang (Next Materials)
Polymer/ceramic composite solid electrolyte is an effective solution for the development of flexible solid-state lithium metal batteries. In this paper, a solid-state lithium-ion electrolyte composed of ceramic powder Li7La2.5Ce0.5Zr1.625Bi0.3O12 (LLCZBO) and lithium salt LiTFSI is added to PVDF-PEO. With the addition of 20 wt% LLCZBO, the electrolyte has a high ionic conductivity of 3.67 × 10−4 S·cm−1 at room temperature. The lithium symmetric battery can be cycled for a long time at a current density of 0.1 mA·cm−2. The battery with LiNi0.6Co0.2Mn0.2O2 (NCM) as the cathode can be cycled at room temperature at 0.1 C and obtain high coulombic efficiency. The excellent cycle performance and rate capability can be attributed to the high ionic conductivity of LLCZBO. These advantages indicate that the composite solid electrolyte (CSE) membranes is expected to be a perfect electrolyte for the next generation of solid-state lithium batteries.